The effects of conditional cash transfers on social engagement and trust in institutions: evidence from Peru's Juntos Programme - Luis A. Camacho (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Conditional cash transfer (CCT) programmes have rapidly expanded throughout the developing world. These programmes have been relatively effective at improving living standards and producing behavioural changes expected to improve human capital among beneficiary children. Little is known, however, about the effect of CCTs on outcomes other than those they intend to modify but which may nonetheless be important for achieving these programmes' longer-term objectives and improving development prospects more generally. This paper addresses this gap by evaluating the effects of CCTs on membership in social organisations and trust in institutions, using evidence from Peru's Juntos programme. The analysis employs household- and district-level data and a difference-in-differences strategy to estimate the programme effects, focusing on the 133 districts in which the programme was implemented during 2006. Its effects among both eligible and non-eligible households are estimated. The programme does not have effects on membership in social organisations on either group of households. It increases trust in institutions related to programme conditions among the eligible population, but it decreases trust in the ombudsman's office, a public institution that has channelled grievances arising from exclusion from the programme. While the results regarding eligible households are encouraging news for proponents, those pertaining to non-eligible households reveal a negative unintended consequence that should be a source of concern.
Keywords: 330; Governance; Soziale Sicherung und Inklusion